The significance of Mendeley usage on the accuracy of citation and references - Iskandar; Andi Anto Patak (International Journal of Humanities and Innovation (IJHI), 2019)
The purpose of this study is to find out the importance of Mendeley reference management software for the accuracy of citation writing and reference lists. This research method is qualitative, using a case study approach. This study asks students to write a brief impression about the importance of using citation manager software such as Mendeley in including citations and simultaneously compiling a bibliography. This research was conducted after students were trained using Mendeley. The subjects of this study were thirty-five students from a private college in the suburb of South Sulawesi, Indonesia. Some impressions that appear in this research are citation accuracy, the accuracy of bibliography, synchronization of citations with bibliography, easy synchronization with Digital Object Identifier (DOI) features, and metadata or bibliographic data. Researchers grouped the impressions of students using MindMap software. This research can be concluded that Mendeley reference management software has citation writing accuracy and a significant reference list helps students write papers and or theses.